Study of the functional properties of a fermented milk product based on mare’s milk - E. S. Simonenko; N. V. Kupaeva; S. V. Simonenko; B. M. Manuilov (Пищевые системы, 2022)
In the last few years, there has been a growing interest in the use of mare’s milk for human nutrition as well as in the use of this product for treatment and prevention of diseases such as hepatitis, chronic pathologies of the gastrointestinal tract, tuberculosis and others. The beneficial properties of mare’s milk are determined first of all by its significant differences from ubiquitous cow’s milk. Many studies show that consumption of fermented milk products offers various advantages for health and the use of probiotic cultures in the composition of starters for fermented milk products allows imparting several functional properties to a product. However, kumis is the only available fermented milk product from mare’s milk on the market. Therefore, the development of new fermented milk products based on mare’s milk is topical and highly demanded. Fermented milk products were developed based on mare’s milk and mare’s milk with addition of cow’s milk using the association consisted of the starter for yogurt and the probiotic strain L. rhamnosus F. The aim of the work was to determine functional properties of fermented milk products based on mare’s milk and mare’s milk with addition of cow’s milk by in vitro methods. It was proved that the products had the high total antioxidant capacity, antiradical and antimicrobial activities as well as the low value of atherogenicity (1.22); the ratio of hypocholesterolemic fatty acids to hypercholesterolemic fatty acids is 1.40.